Assessment of fatigue in postpartum women using patient-reported outcome measures: a systematic review utilising Consensus Based Standards for the Selection of Health Measurement Instruments (COSMIN) guidelines. Issue 4 (2nd October 2022) - Ciechanowicz, S.; Pandal, P.; Carvalho, B.; Blake, L.; Van Damme, S.; Taylor, J.; Sultan, P.
ABSTRACT: Background: Fatigue is a burden for a substantial proportion of women in the postpartum period. A wide array of patient-reported outcome measures (PROMs) are used for assessment, which makes comparison of data difficult. Objective: To identify the best PROM for postpartum fatigue using Consensus-Based Standards for the Selection of Health Measurement Instruments (COSMIN) guidelines. Search strategy: We searched Web of Science, Embase, PubMed and CINAHL, with no date limiters, in July 2020 for validated PROMs used to assess fatigue in the postpartum period. Selection criteria: Studies evaluating at least one author-defined domain of postpartum fatigue and one psychometric measurement property of a PROM. Data collection and analysis: An overall rating was assigned based on COSMIN criteria and the quality of evidence was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Main results: We identified 49 validation studies using 18 PROMs in 21, 209 women that evaluated postpartum fatigue. All three fatigue domains (Physical, Mental, Interference) were assessed by four PROMs: Fatigue Assessment Scale (FAS), Brief Fatigue Inventory (BFI), Checklist Individual Strength (CIS) and Fatigue Severity Scale (FSS). The FAS, which is freely available online, was the only PROM to demonstrate adequate content validity and at least a low level evidence of sufficient internal consistency, resulting in a Class A recommendation. Conclusion: The FAS is the best available PROM to assess postpartum fatigue. However, it fails to assess important areas of postpartum recovery. Future studies should aim to develop a more specific PROM for postpartum fatigue.